Filmes biodegradáveis contendo k-Carragena e montmorilonita para imobilização de lipases e aplicação como removedor de manchas de óleo vegetal - Aguiar, Thandara Cristina (2023)
The accumulation of non-renewable materials in the environment is an urgent social problem to be solved and a large part of this problem is associated with the use of non-biodegradable industrial packaging such as plastic, aluminum, metals, among others. Impositions arising from the socio-environmental context stimulate the innovation of products and industrial processes that enable the reduction of these environmental impacts. Currently, many studies on the use of eco-friendly and biodegradable materials for enzyme immobilization are being studied. The present work proposes the production, characterization and application of biodegradable films based on starch (AM), polyvinyl alcohol (PVOH), κ-Carrageenan (κ-Car) and montmorillonite nanoclay (MMT), to immobilize lipases from Burkholderia lata LBBIO-BL02. Production was carried out using the casting technique, using glycerol as a plasticizer (20% v/m in relation to polymers) and three formulations were prepared: AM-PVOH (AM:PVOH 80:20%); AM-PVOH-κ-Car (AM:PVOH:κ-Car 60:20:20%) and AM-PVOH-κ-Car-MMT (AM:PVOH:κ-Car 60:20:20 and 0.6% of MMT). The lipase was immobilized by physical adsorption, using the sandwich technique. The immobilization efficiency of the films: AM-PVOH, AM-PVOH-k-Car and AM-PVOH-k-Car-MMT was 89%, 93% and 97% and the activity retention was 593%, 730% and 650% respectively. The films had thicknesses between 0.19 and 0.31 μm and AM-PVOH is more flexible than the other films, showing a 45% decrease in flexibility after immobilization. The results show that the most durable and resistant film to act as a support for the immobilization of B. lata is AM-PVOH-κ-Car-MMT. The most solublefilm in water and n-hexane was AM-PVOH (56%) and AM-PVOH-κ-Car (16%), respectively. Scanning electron microscopy (SEM) showed that there were changes only on the surface of the films after the immobilization process. Analysis by Fourier transform infrared spectroscopy (FTIR) coupled with an attenuated total reflectance (ATR) accessory showed characteristic spectra of the materials that make up the films and the free enzyme, with no differences for the spectra of the films with or without lipase. Through thermogravimetric analysis (TGA) it was possible to verify that the AM-PVOH film has greater stability in the main degradation stage, in relation to other films. After immobilization, the films showed less mass loss at maximum degradation. It was possible to apply the films to remove soybean oil stains on cotton fabrics and the highest cleaning efficiency was observed for the AM-PVOH-k-Car-MMT-Lip film, with 76.2% oil removal.